Genetic analysis and counseling of ADPKD caused by novel heterozygous mutations of PKD1 in two Chinese families: Case report - Yanan Wang; Jiapei Jin; Yuqiong Chai; Pai Zhang; Weiwei Zang (Heliyon, 2024)
Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary kidney disease, characterized by the progressive formation of multiple cysts in both kidneys, destruction of the renal structure, changes in renal function and eventually leading to end-stage renal failure and renal transplantation. In our study, Whole-exome sequencing (WES) was used to identify the responsible mutation of ADPKD in two unrelated Chinese PKD families. The WES revealed three variants in the PKD1 gene, c.9857T > C in family 1, c.9860T > G and c.3496G > A in family 2. The comprehensive analysis of population frequency, conservation, structural prediction, and pathogenicity prediction by multiple software suggests that c.9857T > C and c.9860T > G in the PKD1 gene are the primary causes of occurrence and inheritance of ADPKD in family 1 and family 2, respectively. Due to the significant genetic heterogeneity of ADPKD, it’s necessary to understand molecular mechanisms further and collect more data on gene mutations that cause ADPKD. The newly discovered PKD1 variant in this study can expand the database of gene variants and understanding of ADPKD, and provide valuable information for accurate diagnosis and genetic counseling of ADPKD families.